CRIMINAL SANCTION IN ADMINISTRATIVE LAW: A RIGHT WAY TO GO?(APPLYING CRIMINAL SANCTION IN ADMINISTRATIVE ACT) - Naibaho, Nathalina (Tadulako Law Review, 2019)
This article is questioning the problems of formulating criminal sanction in administrative act to solve legal problems in economic activities. This discussion is important, particularly with respect to the heterogeneity of regulations in economic activities. This research argues that this heterogeneity creates legal uncertainty which in turn broader discretion in resolving legal problems in economic activities. This paper will identify the criteria of the offense, which should have criminal sanctions and/or administration in practice law by conducting a review of development of the offenses and sanctions that will influence criminal law in the future.